Transformative Learning in Nicaragua: A Retrospective Analysis of University Agriculture Students’ Long-Term Changes in Perspective After a Study Abroad Course - Janiece Pigg; Adam M. O’Malley; Richie Roberts; Kristin S. Stair (Journal of International Agricultural and Extension Education, 2021)
Study abroad courses have become a priority for institutions of higher education because of a need to broaden students’ perspectives of the world. However, a dearth of knowledge existed regarding whether the reported outcomes of study abroad courses, such changes to students’ perspectives, endure over time. In response, this retrospective study explored how university agriculture students’ (n = 5) shared experiences during a one-week study abroad course to Nicaragua influenced their long-term changes in perspective after returning to the U.S. in 2018. Through our phenomenological analysis, three themes emerged: (1) dichotomous learning outcomes, (2) recognition of power and privilege, and (3) advocacy for global experiences. In the first theme, dichotomous learning outcomes, participants’ long-term changes in perspective appeared to vary based on their level of academic maturity. Meanwhile, in the second theme, as university agriculture students compared their lived experiences in Nicaragua to their existing assumptions of the U.S., it appeared to elicit powerful shifts concerning how they viewed the world. And, as a result, they reported their experiences prompted them to consider the implications of social inequities more deeply. In the final theme, participants reported that after returning home, they began to advocate for global experiences among their peers, family, and friends. Consequently, our findings supported the use of short-term study abroad courses to foster a positive transformation in students’ global perspectives and behaviors after returning to the U.S.
Keywords: agricultural education; study abroad; phenomenology; retrospective long-term change